Epoxidation of Soybean Oil Over Mesoporous Moo3/Ti-sba-15 and Ti-Sba Catalysts - Taş, Canan; Yılmaz, Selahattin (Izmir Institute of Technology, 2018)
In this study, it was aimed to develop heterogeneous acidic mesoporous catalysts for epoxidation of soybean oil. For this, Ti-SBA-15 catalysts were prepared by hydrothermal synthesis with two Si/Ti molar ratios (10, 20). MoO3/Ti-SBA-15 catalyst were prepared by impregnating on the prepared Ti-SBA-15 catalysts. Two different loadings (8 and 12 %) were performed. The soybean oil epoxidation tests were performed in Radley multistation glass reactor system by hydrogen peroxide in ethyl acetate at 75 °C with stirring rate of 900 rpm. For comparison purposes, homogeneous catalysts tests were also performed with H2SO4. The catalyst were found to have mesoporous structure. Titania was succesfully incorporated in to SBA-15. Increasing titania content did not change acidity significantly. Loading of MoO3 decreased the surface area of Ti-SBA-15. Molybdenum loading increased the acidity of the catalysts. The acidity of MoO3/Ti-SBA-15 with 8 % wt MoO3 loading and 10 Si/Ti mole ratio was the highest. The catalysts showed different activities in epoxidation of soybean oil. Some catalysts deactivated. Others showed that the soy bean oil conversion and selectivity to epoxides increased with the acidity of the catalysts. The most active and selective catalyst was found to be 8% MoO3/Ti-SBA-15(10) which gave 35.6 % soybean oil conversion and 35.6 % selectivity to epoxides.

Bu çalışmada, soya yağının epoksidasyonu için asidik mezogözenekli heterojen katalizörler geliştirilmesi amaçlanmıştır. Bunun için, Ti-SBA-15 iki farklı Si/Ti mol oranlarında hidrotermal sentez ile hazırlanmıştır. MoO3/Ti-SBA-15 katalizörü, hazırlanan Ti-SBA-15 katalizörlerine molibdenumun emdirme yöntemiyle yüklenmesi ile hazırlanmıştır. İki farklı yükleme miktarı (8 % ve 12 %) yapılmıştır Epoksidasyon reaksiyonu testleri etil asetat içinde hidrojen peroksit ile 900 rpm karıştırma hızıyla Radley cam reaktör sisteminde gerçekleştirilmiştir. Karşılaştırma amacıyla, homojen katalizör testleri de H2SO4 ile gerçekleştirilmiştir. Katalizörün mezogözenekli bir yapıya sahip olduğu bulunmuştur. Titania, SBA-15'e başarılı bir şekilde eklenmiştir. Artan titanya miktarı asitliği önemli ölçüde değiştirmemiştir. MoO3'ün yüklenmesi Ti-SBA-15'in yüzey alanını azaltmıştır. TiSBA-15 katalizörlerinin yüzey alanları MoO3/Ti-SBA-15 katalizörlerinden önemli ölçüde daha yüksektir. Molibdenum yüklemesi, katalizörlerin asitliğini arttırmıştır. MoO3/Ti-SBA-15'in asitliği 8 wt% MoO3 ve 10 Si / Ti oranı ile en yüksek olmuştur. Katalizörler, soya yağının epoksidasyonu için farklı aktiviteler göstermiştir. Bazı katalizörler aktifliklerini (deaktive) tepkime de kaybettiler. Diğerleri soya yağı dönüşümünün ve epoksitlere olan seçiciliğin, katalizörün asitliği ile arttığını göstermiştir. En aktif ve seçici katalizör 35.6 % soya yağı dönüşümü ve 35.6 % epoksit seçiciliği veren 8% MoO3/Ti-SBA-15(10) olarak bulunmuştur.
Mezogözenekli Moo3/ti-sba-15 ve Ti-sba-15 Katalizörlerle Soya Yağı Epoksidasyonu
Includes bibliographical references (leaves. 53-54)
Text in English; Abstract: Turkish and English
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2018
Keywords: Epoxidation of soybean oil; Soya yağı epoksidasyonu